Splatoon 3. Splatlands, Volume 1 - Hinodeya, Sankichi; Hurley, Jason A., 1981- (VIZ Media, LLC, 2024)
Goggles's adventures continue in the Splatlands! Goggles travels to the Splatlands, meets an inkling named Braid, and embarks on a fresh series of adventures set in the world of Splatoon!